Heterocycle Formation via Palladium-Catalyzed C–H Functionalization - Mei, Tian-Sheng; Kou, Lei; Ma, Sandy; Engle, Keary M.; Yu, Jin-Quan (Synthesis, 2012)
Heterocyclic compounds are ubiquitous in natural products, pharmaceuticals, and agrochemicals. Therefore, the design of novel protocols to construct heterocycles more efficiently is a major area of focus in organic chemistry. In the past several years, cyclization reactions based upon palladium-catalyzed C–H activation have received substantial attention due to their capacity for expediting heterocycle synthesis. This review discusses strategies for heterocycle synthesis via palladium-catalyzed C–H bond activation and highlights recent examples from the literature.1 Introduction2 Intramolecular Cyclization via C–C Bond Formation2.1 Arene/Arene Coupling2.1.1 C–H Arylation with Aryl Halides2.1.2 C(sp2)–H/C(sp2)–H Coupling2.2 Arene/Alkene Coupling or Arene/Alkyne Coupling 2.2.1 Arene/Alkene Coupling2.2.2 Arene/Alkyne Coupling2.3 Arene/Alkane Coupling2.3.1 C(sp2)–H Alkylation with Alkyl Halides2.3.2 C(sp3)–H Arylation with Aryl Halides2.3.3 C(sp2)–H/C(sp3)–H Coupling3 Intramolecular Cyclization via C–N Bond Formation4 Intramolecular Cyclization via C–O or C–S Bond Formation 5 Incorporation with Carbon Monoxide6 Incorporation with Isonitrile7 Incorporation with Olefin8 Conclusions
Keywords: heterocycle; C–H activation; arylation; alkylation; amination; carbonylation; olefination